Hawaa (peace be upon her) in the narrations of Al-Bayt (peace be upon them) (Journal of Imam Al-Kadhim College, 2023)
The research aims to answer the questions that revolve in the mind of humanity about our mother Eve (peace be upon her) and how she was created? Is her creation independent of Adam? Why was she punished and stayed with Adam? Did she play a role in the seduction? How to find creation from it and from Adam (peace be upon them)? How was the emergence of civilizations since the beginning of creation?The human race is the focus of the completion of those cultures that gave the man priority in being considered the first human model over the woman, who occupied second place in that humanity. This may be due to the fact that the first earthly creature was a man (Adam), or perhaps because the woman was primarily responsible for this idea of descending to earth. The idea that has settled in some cultures, and we will rely in the research on relying on (the Qur’anic text) that presents the story of Adam and Eve (peace be upon them) and on the historical narratives narrated about the Household (peace be upon them).
Keywords: Keywords: (Hawaa'i, Paradise, tree, descent to earth, reproduction of offspring)